Effects of addition of a palmitic sucrose ester on low-trans-fat blends crystallization in bulk and in oil-in-water emulsions - Huck Iriart, Cristián (2009)
The effect of addition of a highly hydrophobic emulsifier, the palmitic sucrose ester P-170, on isothermal crystallization behavior of a high-melting fraction of milk fat (HMF) and its mixtures with 20% or 40% sunflower oil (SFO), both in bulk and in emulsion systems, were studied by nuclear magnetic resonance (NMR) and by time-resolved in situ small-angle synchrotron X-ray scattering (SAXS). NMR studies showed that the effect of P-170 on the overall isothermal crystallization kinetics in bulk phase could be either acceleration or delay. The effect was strongly dependent on supercooling. For HMF, P-170 retarded crystallization at temperatures above 29.0 ± 0.2°C, while below that temperature, it accelerated the process. For the blends of HMF with 20% or 40% SFO, the temperature at which the behavior changed was 27.0 ± 0.2 or 26.0 ± 0.2°C, respectively. In emulsion systems, however, the effect was always acceleration for all temperatures selected. With the aid of SAXS, it was possible to study early stage of crystallization during real time and therefore to improve our understanding of the mechanism of P-170 action. The different effects caused by P-170, as described by SFC curves, were strongly related to the effects of P-170 on fat polymorphism, specially to the value of the time interval of coexistence of the α and β′ forms. These events took place at the very beginning of crystallization and thus could not be described by the traditional X-ray techniques used in previous studies of similar systems.